2020
DOI: 10.1371/journal.pone.0229198
|View full text |Cite
|
Sign up to set email alerts
|

Imaging studies of bacterial biofilms on cochlear implants—Bioactive glass (BAG) inhibits mature biofilm

Abstract: The capability of Pseudomonas aeruginosa and Staphylococcus aureus to form biofilm on varying CI component materials differs in the presence and absence of bioactive glass (BAG). The application of BAG induces significant changes in biofilm morphology which can be visualized via scanning electron microscopy (SEM). Bacterial biofilm formation on medical devices, such as cochlear implants (CI), can lead to chronic infections. Interestingly, BAG of type S53P4 seems to be a promising tool for use in the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, temporal dynamics of the biofilm formation by ocular Staphylococcal spp. from attachment to dispersal phase were rarely monitored [ 53 , 54 , 58 ]. Hou et al [ 54 ] using SEM, observed that ocular biofilm-positive staphylococcal strains go through a phase of adhesion and accumulate as small monolayer sheets which then get transformed into multilayer sheets enclosed in the self-secreted EPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, temporal dynamics of the biofilm formation by ocular Staphylococcal spp. from attachment to dispersal phase were rarely monitored [ 53 , 54 , 58 ]. Hou et al [ 54 ] using SEM, observed that ocular biofilm-positive staphylococcal strains go through a phase of adhesion and accumulate as small monolayer sheets which then get transformed into multilayer sheets enclosed in the self-secreted EPS.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus and S. epidermidis are also commonly found infecting the anophthalmic cavity of ocular prosthesis users [ 51 , 52 ]. Some or all the previous studies on biofilm formation in S. aureus and S. epidermidis used non-clinical strains [ 53 ], whereas, in this study, both S. aureus and S. epidermidis were of clinical origin, isolated from patients with infectious Endophthalmitis. Biofilm formation was monitored by Congo red (CR) method as in the previous studies [ 54 ]; but, for monitoring the temporal dynamics of biofilm formation, we used the Crystal violet (CV) method [ 54 ] and also the XTT method [ 55 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The biofilm forms a microenvironment that supports the bacteria and protects them from host defense systems and antibacterial drugs. As the metabolic activity of biofilm-resident bacteria decreases, their sensitivity to most antimicrobial agents also decreases [ 36 ]. A structured layer of bacterial biofilm is shown in Figure 2 A [ 37 ].…”
Section: Antibacterial Effectsmentioning
confidence: 99%
“…Studies found patterns of biofilm formations for species and materials [111]. There are great examples of bioglass such as S53P4, which contains sodium oxide, phosphorus pentoxide, silicon dioxide, and calcium oxide and has been tested successfully for osteoinduction and reduction of bacteria [112,113].…”
Section: Cochlear Implantsmentioning
confidence: 99%